Padronização do teste de potência de toxóide alfa de Clostridium novyi tipo B em linhagem contínua de célula - Catarina Guimaraes Rocha Dourado Lima (2009)
Clostridium novyi type B is the pathogen responsible for necrotic hepatitis caused by the action oh alpha toxin. The control of this disease is based on immunization of animals with vaccines containing in its composition alpha toxoid of C. novyi type B, and the potency test performed from sera of rabbits immunized by the technique of neutralization in mice. This study aimed to standardize a potency test of alpha toxoid of C. novyi type B in VERO cell line, as an alternative to animal bioassay. The neutralizing antibodies against alpha toxin in Vero cell culture were compared with results obtained by the technique in mice, and can claim no significant difference between the models. The correlation coefficient established between the titers obtained by the in vitro and in vivo tests was 98.38%, indicating a possible use of the model studied in the replacement of animal model for potency test of alpha toxoid of C. novyi type B.